THE USE OF STUDENT TEAM ACHIEVEMENT DIVISIONS IN IMPROVING THE LEARNING OUTCOME IN PHYSICS COURSE - Bandiyah Sri Aprillia , Arinilhaq , Aan Komariah , Mohamad Ramdhani (International Journal of Advanced Science and Technology, 2020)
It has been proven that Student Team Achievement Divisions (STAD) is efficient in helping the students master the delivered materials. It allows the student to intensively interact and help each other discuss the difficulty they face on their own. Therefore, this study aims to enhance learning outcome of Physics course in the Telkom University by using STAD learning model. The This study uses two cycles design consisting of four different activities to assess the learning process of the students. The subject of this research were students taking the physics course in the class of TT 4206 consisting of 31 students. Student achievement increases were noted at the end of the study. It was also confirmed that the percentage of passing was higher than the previous year. The increase of the learning outcome and percentage of passing indicated that the discussion process ran well in terms of doing the assignments in most of the groups. Furthermore, giving varied exercises continuously made the students feel challenged to finish the exercises. Therefore, the learning outcome made an impression for the students.